Does Employee Alignment Affect Business-IT Alignment? An Empirical Analysis - Chong, Alain Yee Loong; Chan, Felix T. S.; Ooi, Keng Boon; Darmawan, Nathan (Taylor & Francis, 2011)
The aim of this paper is to investigate if employee alignment will influence the business-IT alignment in organizations. We measured employee alignment through perceived organizational trust, perceived communications on business-IT strategies to employees, perceived employee commitment to business-IT strategies and perceived knowledge on business-IT strategies. Structural equation modelling (SEM) is used to test the model and hypotheses in this research. The findings from this study indicated that perceived organizational trust, perceived communications on business-IT strategies to employees and perceived knowledge on business-IT strategies have a positive and significant relationship with business-IT alignment of organizations. This study addresses the lack of empirical research by investigating whether employee alignment would improve an organization’s business- IT alignment.